Growth performance of Fragaria x ananassa "Sweet Charlie" to different culture media and varying pH of hydroponic nutrient solution - Lapuz, Mayveline R.; Daquigan, Madonna C. (2014., 2014)
Hydroponics is an alternative way of cultivating crop using water containing essential nutrients fro plant growth. This study focused on comparing the effectiveness of this technique on Fragaria x ananassa at varying pH and concentration of the nutrient solution and compared with the traditional way of cultivating crops using soil from a forest and agricultural land. Results from this study showed that it is possible to grow Fragaria x ananassa in two different hydroponics nutrient solutions and it was observed that plants responded best at pH 6. The response of the plants to pH4, 6 and 8 are statistically different from each other based on the analysis of variance. Comparatively,root length was longer in the hydroponics - reared strawberries relative to plants grown in soil. The results from the hydroponics and the traditional way of crop cultivation of Fragaria x ananassa are statistically different based of the growth performance -- Author's abstract.
Thesis (Bachelor of Science in Biology)--University of the Philippines, 2014.
Includes bibliographical references (leaves 49-52).
Keywords: Hydroponics; Strawberries -- Growth